2007
DOI: 10.1002/jmv.20834
|View full text |Cite
|
Sign up to set email alerts
|

Ongoing subclinical infection of hepatitis E virus among blood donors with an elevated alanine aminotransferase level in Japan

Abstract: Ongoing subclinical infection of hepatitis E virus (HEV) has not been fully studied. In the present study, serum samples were collected from 6700 voluntary blood donors with an elevated alanine aminotransferase (ALT) level of 61-476 IU/l at a Japanese Red Cross Blood Center, and were tested for the presence of IgG, IgM and IgA classes of antibodies to HEV (anti-HEV) by in-house ELISA and HEV RNA by nested RT-PCR. Overall, 479 blood donors (7.1%) were positive for anti-HEV IgG, including 8 donors with anti-HEV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
65
0
3

Year Published

2008
2008
2018
2018

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 47 publications
6
65
0
3
Order By: Relevance
“…The seroprevalence rates observed in this study (donors with nonelevated ALT, 6%; donors with elevated ALT, 5.88%) are more comparable to rates which have been observed for Switzerland and Japan than to those observed for Germany so far. The seroprevalence rates of anti-HEV IgM have been measured less frequently, but studies in Chinese blood donors revealed a seroprevalence rate of 0.94 to 1.8% (11,21), comparable to 0.5 to 1.6% in Japan (18,20,42) and the 0.5% observed in this study. We also observed a considerably higher seroprevalence rate of 8.08% in donors with elevated ALT levels, according to data obtained by Fukuda et al (3.3%) (18).…”
Section: Discussionsupporting
confidence: 57%
“…The seroprevalence rates observed in this study (donors with nonelevated ALT, 6%; donors with elevated ALT, 5.88%) are more comparable to rates which have been observed for Switzerland and Japan than to those observed for Germany so far. The seroprevalence rates of anti-HEV IgM have been measured less frequently, but studies in Chinese blood donors revealed a seroprevalence rate of 0.94 to 1.8% (11,21), comparable to 0.5 to 1.6% in Japan (18,20,42) and the 0.5% observed in this study. We also observed a considerably higher seroprevalence rate of 8.08% in donors with elevated ALT levels, according to data obtained by Fukuda et al (3.3%) (18).…”
Section: Discussionsupporting
confidence: 57%
“…Similar isolates as G3 Unclassified from one (swJR-C9) of the two farms were also previously reported in Japan [19,30].…”
Section: Phylogenetic Analysis Of Swine-derived Hevs With Reported Swsupporting
confidence: 55%
“…In Japan, HEV RNA has been detected in blood donors with elevated liver enzymes (12). A recent report from France found that acute HEV in persons who had not traveled to HEV-endemic regions may cause fulminant hepatitis, especially in those with active alcohol use and other chronic liver disease (13).…”
Section: Discussionmentioning
confidence: 99%